Use of aerial photograph to enhance dog population census in Ilorin, Nigeria (2012)
The ground survey method for dog population census is considered to be prone to error in enumeration. As a result, use of aerial photography has been suggested as capable of enhancing ground survey methods for more accurate results. Dog population census was carried out within llorin city in October 2010 using direct street count and questionnaire survey aided by coverage precision of the 2010 aerial photograph of the city to define enumeration areas. The city was classified into three functional zones, namely residential (low, medium and high income areas) non-residential (educational, government offices, commercial and recreational areas) and transit zones (vehicle terminals for cars, buses and trucks traveling from southwestern to northern parts of Nigeria and vice versa). Five hundred questionnaires were administered to obtain primary data on socio-economic characteristics of dog owners and dog count. A total of 16,348 households were covered in the city. Dog population was estimated to be 1,258 comprising 668 (53.10%) male and 590 (46.90%) female. There were 356 (28.30%) young dogs (<6 month old) and 902 (71.70%) adult dogs (> 6 months old) in the population. Dog distribution ranged from 510 (40.54%) in non-residential areas and 480 (38.16%) in residential areas, to 268 (21.30%) in transit areas of the city. Dog population density of 1:13 dog per household was obtained. Poorly managed garbage collection points were found to be associated with and aid the distribution of roaming dogs. The census figures generated in this study are valuable for public health planning in Ilorin, Nigeria, particularly for antirabies control programme among dogs in the city.